Sovereign forces : everyday challenges to environmental governance in Latin America - McNeish, John-Andrew (Berghahn Books, 2021)
"Sovereignty is a significant force regarding the ownership, use, protection and management of natural resources. By placing an emphasis on the complex intertwined relationship between natural resources and diverse claims to resource sovereignty, this book reveals the backstory of contemporary resource contestations in Latin America and their positioning within a more extensive history of extraction in the region. Exploring cases of resource contestation in Bolivia, Colombia and Guatemala, Sovereign Forces highlights the value of these relationships to the practice of environmental governance and peacebuilding in the region"--